2013
DOI: 10.1016/j.cell.2013.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Gle1 Functions during mRNA Export in an Oligomeric Complex that Is Altered in Human Disease

Abstract: The conserved multifunctional protein Gle1 regulates gene expression at multiple steps: nuclear messenger (m)RNA export, translation initiation, and translation termination. A GLE1 mutation (FinMajor) is causally linked to human lethal congenital contracture syndrome-1 (LCCS1); however, the resulting perturbations on Gle1 molecular function were unknown. FinMajor results in a Proline-Phenylalanine-Glutamine peptide insertion within the uncharacterized Gle1 coiled-coil domain. Here we find that Gle1 self-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
114
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(121 citation statements)
references
References 54 publications
6
114
1
Order By: Relevance
“…These include SMN in SMA, GLE1 in LCCS1 and TARDBP, FUS and GLE1 in ALS (Lefebvre et al, 1995, Sreedharan et al, 2008, Nousiainen et al, 2008, Vance et al, 2009, Folkmann et al, 2013. Interestingly, all have been implicated in multiple aspects of RNA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These include SMN in SMA, GLE1 in LCCS1 and TARDBP, FUS and GLE1 in ALS (Lefebvre et al, 1995, Sreedharan et al, 2008, Nousiainen et al, 2008, Vance et al, 2009, Folkmann et al, 2013. Interestingly, all have been implicated in multiple aspects of RNA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Whether mRNA export defects represent a disease-relevant mechanism in ALS cases caused by C9orf72, and how this process might influence the formation of RAN peptides from C9orf72 translation, an important contributing factor to C9orf72 toxicity, obviously needs further investigation. However, motor neurons seem to be particularly sensitive to alterations in this process, as mutations in the human GLE1 gene, that has a central function in nuclear mRNA export, are responsible for the autosomal recessive lethal congenital contracture syndrome-1 (LCCS1), a disease characterized by lack of anterior horn motor neurons and severe atrophy of the ventral spinal cord (Folkmann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The mutation in human GLE1 is causally linked to human lethal congenital contracture syndrome-1. 41 In our study, we found the Atgle1 mutation gives approximately 19% seed abortion in the heterozygous plants (AtGLE11/Atgle1), 24 suggesting its mutation is not homozygous lethal. However, when we tried to isolate the homozygous mutant (Atgle1/Atgle1), we were not successful after genotyping more than 200 plants from the heterozygous plant (AtGLE11/Atgle1) progeny.…”
Section: Discussionmentioning
confidence: 86%
“…40 The Gle1 protein contains predicted coiled-coil domain and IP 6 binding domain for regulating DEDA-box proteins (Dbp5 in yeast, DDX19 in human, or LOS4 in plants). 41 By interacting with the small molecule IP 6 , Gle1 stimulates ATPase activity of Dbp5. 42,43 Then Gle1/IP6-activated Dbp5 is converted from a Dbp5-ATP to Dbp-ADP state that causes mRNP remodeling, thus facilitating export directionality.…”
Section: Discussionmentioning
confidence: 99%